PTH-046 Double-balloon enteroscopy assisted cyanoacrylate injection therapy of small-bowel varices: international experience from two european centres. (8th June 2018) - Murino, Alberto; May, Andrea; Lazaridis, Nikolaos; Koukias, Nikolaos; Vlachou, Erasmia; Planche, Katie; Patch, David; Despott, Edward J
Abstract : Introduction: Small bowel varices (SBV) are a rare consequence of portal hypertension and could lead to life-threatening mid-gut bleeding. Radiological intervention (RI) is usually considered first line management (e.g. Trans-jugular intrahepatic portosystemic shunting (TIPS), stenting of occluded mesenteric veins±embolisation of culprit varices). In cases where RI is impossible, management options become very limited. This multicentre case series evaluated the usefulness of double-balloon enteroscopy (DBE) assisted cyanoacrylate injection of SBV. Methods: Retrospective review of DBE facilitated cyanoacrylate injection of SBV (December 2015 to October 2016). Demographic, clinical, endoscopic and radiological findings, interventions and follow-up data were analysed. Results: Ten DBEs were performed in 6 patients (4 women, median age: 68.5 years). Five patients had previous surgery (hemi-hepatectomy (n=2); SB resection (n=2); appendicitis with peritonitis (n=1)); one patient had a history of intra-abdominal sepsis in childhood causing portal vein thrombosis and one had cryptogenic thrombosis of the portal and the mesenteric vein. No radiological or surgical options were deemed feasible in any case. SBV were diagnosed at capsule endoscopy and triple phase CT mesenteric angiography. At DBE, a total of 13 nests of SBV were identified and injected with cyanoacrylate glue. There were no haemorrhagic or embolic complications but 1 patient developed an infection of a congenital urachal cyst, which was treated successfully with antibiotics. All patients underwent DBEs via the anterograde route, 2 patients required bi-directional DBE for treatment of both proximal and distal SBV and in total 2 patients required a repeat DBE for further treatment of SBV. At 30 day follow-up post-therapy, only 1 patient had experienced a mild recurrence of mid-gut bleeding treated conservatively. One patient presented with acute gastrointestinal bleeding 7 months later and a repeat DBE with cyanoacrylate injection therapy was successfully performed. One patient was lost to follow-up. The remaining patients had 12 months of follow-up without any recurrent gastrointestinal bleeding. Conclusion: Cyanoacrylate injection therapy of SBV at DBE appears to be a safe and effective management strategy for this condition when other first-line options are not feasible.